Estudo do desempenho do receptor de imagem em mamografia digital contrastada utilizando simulações Monte Carlo. - Assis, Cesar Augusto Silva Cardoso (2021)
Breast cancer is one of the main cause of cancer death among women, and mammography exams are the only imaging technique that has shown to reduce such mortality. However, mammography has limitations, especially in dense or thick breasts, in which the identification of nodules or microcalcifications may be obscured by breast tissue. Recently, the contrast-enhanced mammography technique has shown a great potential as a complementary imaging technique to identify alterations in screening mammography. In this technique, an iodine-based contrast agent is administred intravenously, allowing the administered contrast agent to circulate throughout the breast blood vessels, highlighting possible malignant nodules. In dual-energy contrast-enhanced mammography, images are acquired with low- and high-energy radiation beams, and the two images are then subtracted, providing an increase in the contrast agent in relation to the breast tissue. The quality of the mammography image depends, among other factors, on the performance of the image receptor with respect to spatial resolution and on the modulation transfer function (MTF), which quantifies the reduction in contrast at the spatial frequency domain, is considered the most appropriate function to evaluate the spatial resolution of the imaging system. The objective of this work is to study the different types of image receptors (a- Se and CsI) in order to evaluate how different acquisition factors can influence image quality. This study was done by obtaining the MTF x curves, acquired through simulations using the Monte Carlo code PENELOPE. The performance of direct conversion (a-Se) receivers and indirect conversion (CsI) receptors were analyzed considering low and high energy beams employed in contrast mammography. Results showed that, with the increase of the tube potential, the MTF x curves improve for a-Se, while for CsI there was a reduction in MTF x , especially for beams with energies above the absorption K-edge of the receptor. The increase of receptor thickness causes a reduction in MTF x , due to the increased probability of multiple interactions occurrence and of the reabsorption of produced characteristic radiation by the receptor. It was not observed significant results for the influence of beam attenuation by the breast on the MTF x curves. For the pre-sampling MTF curves, it was observed that geometric effects due to the dimensions of the surface of the detector elements are the main cause of limitation of the image’s spatial resolution, with less influence of the radiation interactions. The results obtained in the present study were compared with experimental data from the literature, showing good agreement, indicating the feasibility of using computational methods for simulating the radiation transport in the receptor for the study of the imaging systems performance in contrasted-enhanced mammography technique.